2018
DOI: 10.1038/s41598-018-33885-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of inverted and upright laser-activated titanium nitride micropyramids for intracellular delivery

Abstract: The delivery of biomolecules into cells relies on porating the plasma membrane to allow exterior molecules to enter the cell via diffusion. Various established delivery methods, including electroporation and viral techniques, come with drawbacks such as low viability or immunotoxicity, respectively. An optics-based delivery method that uses laser pulses to excite plasmonic titanium nitride (TiN) micropyramids presents an opportunity to overcome these shortcomings. This laser excitation generates localized nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…The microscopic observation of the laser surface texturing of the samples after modification by the PVD method showed a coarse ablated surface, where the edge of the groove appears to be continuous; only a few corrugated grooves with chunks of residues scattered inside the groove and the heat-affected zone on the treated surfaces have also been observed. In the position close to the edge of the hexagon there is a little accumulation of the molten matters, which leads to a convex structure [27,58,59].…”
Section: Discussionmentioning
confidence: 99%
“…The microscopic observation of the laser surface texturing of the samples after modification by the PVD method showed a coarse ablated surface, where the edge of the groove appears to be continuous; only a few corrugated grooves with chunks of residues scattered inside the groove and the heat-affected zone on the treated surfaces have also been observed. In the position close to the edge of the hexagon there is a little accumulation of the molten matters, which leads to a convex structure [27,58,59].…”
Section: Discussionmentioning
confidence: 99%
“…This was achieved with a throughput of 50 000 cells/min. In another study, Raun et al used a similar set-up but replaced gold by a thin titanium nitride coating thereby presenting a higher melting temperature, which could render improved stability of the film over time [51]. A recent study by Zhao et al reported a large plasmonic array with gold square-shaped 'nanodisks', demonstrating again that, after 6 ns 532 nm laser pulses, thermal-induced VNBs are formed at the plasmonic hotspots, this time situated at the corners of each nanodisk (Figure 4D) [52].…”
Section: Photothermal Substratesmentioning
confidence: 99%
“…Many devices have been created for cargo delivery, including devices that use squeezing as the physical mechanism, microcapillary pipettes for microinjecting cargo, microfluidic devices, and plasmonic materials for cell poration. Plasmonic poration of cells has been demonstrated using metallic nanoparticles and a variety of substrates made of titanium nitride, gold, and titanium, such as pyramidal arrays fabricated using photolithography and nanocavity structures fabricated using self-assembling colloids; however, metals used in nanophotothermolysis can fragment . To avoid the risk of metallic fragmentation from thin films and nanoparticles, it is important to explore other nonmetallic thin-film materials.…”
Section: Introductionmentioning
confidence: 99%